Pengaruh Shopping Lifestyle, Kepercayan Konsumen Dan Label Halal Terhadap Keputusan Pembelian Terhadap Produk Wardah. - Ririz Della Nur Aini; Siti Asiyah; Rahmawati Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract    His study aims to determine the influence of shopping lifestyle, consumer trust and halal labels on purchasing decisions on Wardah products. This study used a type of quantitative research. The sampling technique used the maholtra formula and obtained the results of 80 respondents. Data collection was carried out using questionnaires. The data analysis methods used in this study are Instrument Test (validity test and reliability test), Normality Test, Classical Assumption Test (multicollinearity test and heteroscedasticity test), Multiple Linear Regression Analysis, Hypothesis Test (f test), and (t test), Coefficient of Determination (Adjusted R2) and the analysis process using SPSS. From the results of partial research, it was found that shopping lifestyle has a significant effect on purchasing decisions, consumer confidence has a significant effect on purchasing decisions and halal labels have a significant effect on purchasing decisions. While simultaneously shopping lifestyle, consumer trust and halal labels have a significant influence on purchasing decisions Keywords: Shopping lifestyle, Consumer Trust, Halal Label, Purchase Decision